Human mitochondrial RNA turnover caught in flagranti: involvement of hSuv3p helicase in RNA surveillance - Szczesny, Roman J. (Oxford University Press, 2010)
The mechanism of human mitochondrial RNA turnover and surveillance is still a matter of debate. We have obtained a cellular model for studying the role of hSuv3p helicase in human mitochondria. Expression of a dominant-negative mutant of the hSUV3 gene which encodes a protein with no ATPase or helicase activity results in perturbations of mtRNA metabolism and enables to study the processing and degradation intermediates which otherwise are difficult to detect because of their short half-lives. The hSuv3p activity was found to be necessary in the regulation of stability of mature, properly formed mRNAs and for removal of the noncoding processing intermediates transcribed from both H and L-strands, including mirror RNAs which represent antisense RNAs transcribed from the opposite DNA strand. Lack of hSuv3p function also resulted in accumulation of aberrant RNA species, molecules with extended poly(A) tails and degradation intermediates truncated predominantly at their 3′-ends. Moreover, we present data indicating that hSuv3p co-purifies with PNPase; this may suggest participation of both proteins in mtRNA metabolism.